Genetic analysis and mapping of ascochyta blight resistance in kabuli chickpea (Cicer arietinum) - LOVEPREET KAUR; AJINDER KAUR; PALVI MALIK; SARVJEET SINGH; UPASANA RANI; YOGESH VIKAL; INDERJIT SINGH; PRITI SHARMA (The Indian Journal of Agricultural Sciences)
Ascochyta blight is a fungal disease of chickpea (Cicer arietinum L.) caused by Ascochyta rabiei, resulting in up to 100% crop yield loss under favourable conditions. The experiment was conducted during 2018–19 and 2019–20 at Punjab Agricultural University, Ludhiana, Punjab aimed to transfer ascochyta blight resistance, a commercially important susceptible kabuli cultivar L 552 was crossed with an exotic resistant kabuli line FLIP 05-43. The F2 and F2:3 populations developed from L 552 × FLIP05-43 cross were screened for ascochyta blight resistance using cut twig method at Punjab Agricultural University, Ludhiana. Genetic studies in these populations revealed that resistance to the disease was controlled by single recessive gene designated as arr6. The genotyping of F2 population was carried out using 46 polymorphic SSR markers. The linkage analysis mapped 31 markers into eight linkage groups with a total map length of 377.14 cM. The gene arr6 was located on LG 4 at a distance of 8.6 and 16.1 cM from markers CGMM072 and NCPGR247, respectively. Thus, the present study identifies genomic location of the gene conditioning resistance to ascochyta blight. The detected region will further be fine mapped to follow marker assisted breeding for ascochyta blight resistance. To our best knowledge, this is the first report of mapping arr6 gene using kabuli line FLIP05-43.